2012
DOI: 10.1088/0967-3334/33/3/n19
|View full text |Cite
|
Sign up to set email alerts
|

Supersonic shear imaging provides a reliable measurement of resting muscle shear elastic modulus

Abstract: The aim of the present study was to assess the reliability of shear elastic modulus measurements performed using supersonic shear imaging (SSI) in nine resting muscles (i.e. gastrocnemius medialis, tibialis anterior, vastus lateralis, rectus femoris, triceps brachii, biceps brachii, brachioradialis, adductor pollicis obliquus and abductor digiti minimi) of different architectures and typologies. Thirty healthy subjects were randomly assigned to the intra-session reliability (n = 20), inter-day reliability (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

33
187
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 204 publications
(227 citation statements)
references
References 35 publications
33
187
7
Order By: Relevance
“…These results are close to those provided by Lacourpaille et al (2012), who found intra-operator repeatability lower than 6% and inter-operator reliability lower than 11.5%. Values measured by Lacourpaille et al (2012) were lower of about 1 kPa compared to those presented in this study at rest (GM: 2.99 vs 4.7, VL: 3.26 vs 4.5, RF: 3.23 vs 4.1). Both studies were performed on homogeneous population healthy young subjects.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These results are close to those provided by Lacourpaille et al (2012), who found intra-operator repeatability lower than 6% and inter-operator reliability lower than 11.5%. Values measured by Lacourpaille et al (2012) were lower of about 1 kPa compared to those presented in this study at rest (GM: 2.99 vs 4.7, VL: 3.26 vs 4.5, RF: 3.23 vs 4.1). Both studies were performed on homogeneous population healthy young subjects.…”
Section: Discussionsupporting
confidence: 91%
“…This was accompanied by a measured increase in shear modulus which was observed during preliminary tests. A similar phenomenon was previously observed by Lacourpaille et al (2012), but such increase in modulus was eliminated by asking the subject to freely strech out and walk between each series of measurement.…”
Section: Complete Protocolsupporting
confidence: 65%
See 2 more Smart Citations
“…Precision values were similar to those obtained in vitro in animal specimens (Vergari et al, 2014) (7 % repeatability in unloaded discs) and in vivo in muscles (Lacourpaille et al, 2012). Measurements in breast phantom have been previously performed with a slightly higher precision error of 0.5 m/s (corresponding to 0.82 kPa in Young's modulus) (Mun et al, 2013).…”
Section: Fig 5 (A)supporting
confidence: 80%